Do Recruiters Penalize Men Who Prefer Low Hours? Evidence from Online Labor Market Data - Daniel Kopp (Institute of Labor Economics (IZA), 2024)
Part-time work is a popular way to reconcile work and family responsibilities. This study investigates how easy it is for men and women to get part-time jobs. To assess this question, I first analyze the hiring decisions of recruiters who screen jobseekers on an online recruiting platform and estimate contact penalties for men and women seeking part-time jobs. Second, I relate the number of hours advertised in online job postings to firms' confidentially reported gender preferences. I find that recruiters prefer full-time over part-time workers, and that part-time penalties are more pronounced for men than for women. Differences in job or workplace characteristics cannot explain these results. Instead, the preponderance of evidence points to bias due to gender stereotypes.
Keywords: J16; J23; M51; 330; recruitment; part-time; gender equality; hiring; online labor markets